Externalities and subsidization of higher education - Stefan Winter; Alexander Pfitztner (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Higher education is subsidized worldwide, although with pronounced differences in levels of subsidization. While public funds account for about 90% of universities budgets in Scandinavian countries, the share of public funds in Great Britain and the US is less that 30%. Subsidization is typically justified by two arguments: It is necessary to enable children from poorer family backgrounds to join universities. The other argument holds that higher education is accompanied by positive externalities. Without subsidization, so the story reads, there would be an underinvestment in higher education. This paper shortly reviews theoretical arguments as well as empirical evidence on externalities. It is found that evidence on positive externalities is quite limited. What is more, evidence on negative externalities of higher education has been mainly ignored so far. If potential losses due to negative externalities are taken into account, there may be much more reason to suppress higher education than there is reason to subsidize it. If subsidization is reasonable at all, it will be reasonable in special cases only. We present a simple model of optimal subsidization and evaluate existing subsidization regimes in the US, Australia and Germany. We demonstrate that any of these regimes has severe shortcomings even if positive externalities are assumed to exist. While the Australian regime of income contingent loans is relatively best, it still offers many opportunities for improvement. We offer some guidance on potential improvements.
Keywords: D62; I21; I28; 330